Sub-brachialis course of the median nerve in the arm and its possible clinical complications: a case report - Melanie, RD; Anitha, G; Naveen, K; Satheesha, BN (Department of Surgery, UKM Medical Centre, 2012)
The median nerve in its normal course in the arm crosses the brachial artery from lateral to medial side. It then passes superficial to the brachialis muscle and then enters the cubital fossa. During routine cadaveric dissection of the right upper limb, an unusual variation in the course of the median nerve was observed. The median nerve in the arm crossed the brachial artery from medial to lateral side and passed deep to the brachialis muscle. It then emerged from beneath the brachialis muscle and entered the cubital fossa. In the cubital fossa, it ran medial to the brachial artery as the normal course of the nerve. Further distribution of median nerve in the forearm and hand was observed to be normal. The anomaly reported here may result in the compression of the median nerve deep to the brachialis and hence resulting in mechanical disadvantages in the flexion at the wrist joint.